2010
DOI: 10.1021/jz101378z
|View full text |Cite
|
Sign up to set email alerts
|

Water Adsorption on Coordinatively Unsaturated Sites in CuBTC MOF

Abstract: We report a theoretical study of water adsorption on coordinatively unsaturated sites (cus's) in a metal−organic framework (MOF) compound CuBTC. The reliability of the density functional theory (DFT)-based methods and dispersion-corrected DFT-D schemes for the description of cus sites was investigated with respect to the accurate reference CCSD(T)/CBS data. The accuracy of both DFT and DFT-D methods was found to be insufficient. The proposed DFT/CC correction scheme gave the results in excellent agreement with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
218
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(242 citation statements)
references
References 41 publications
22
218
2
Order By: Relevance
“…This cluster was found to provide identical results to those obtained with much larger cluster models. 103 It was found that the combination of the predicted interaction enthalpies in very good agreement with the benchmark result calculated by Grajciar et al 101 The water to Cu and the Cu-Cu distances are quite different from functional to functional. The fact that the M06-2X yields almost as good results as the M06-L or M06 functionals is surprising since the latter were suggested to be better than the former for systems containing transition metal elements.…”
Section: Molecular Adsorptionsupporting
confidence: 71%
See 1 more Smart Citation
“…This cluster was found to provide identical results to those obtained with much larger cluster models. 103 It was found that the combination of the predicted interaction enthalpies in very good agreement with the benchmark result calculated by Grajciar et al 101 The water to Cu and the Cu-Cu distances are quite different from functional to functional. The fact that the M06-2X yields almost as good results as the M06-L or M06 functionals is surprising since the latter were suggested to be better than the former for systems containing transition metal elements.…”
Section: Molecular Adsorptionsupporting
confidence: 71%
“…It was found that standard DFT methods are inadequate for describing the interaction of organic molecules with those metal sites very probably due to difficulties in the correct description of the dispersion interactions between the adsorbate and the MOF organic parts. In fact, in recent studies by Grajciar et al 101 it was found that BLYP, PBE, TPSS and B3LYP underestimate significantly the interaction energies for water with HKUST-1, a MOF with copper open metal sites based on copper ''paddle-wheels'' connected by benzene 1,3-5-tricarboxylate linkers (Fig. 11).…”
Section: Molecular Adsorptionmentioning
confidence: 98%
“…The transition states from the extended cluster calculations were taken as starting geometries to find the transition states in the periodic model. An optimized Cu-BTC unit-cell was obtained from Nachtigall et al [61] and was reoptimized with periodic DFT-D2 calculations. For those simulations, the Brillouin zone was restricted to the Г-point.…”
Section: Periodic Calculationsmentioning
confidence: 99%
“…The separation of flue gas, however, requires thermodynamic information (for example, adsorption isotherms) at flue-gas conditions (40 8C and 1 atm). This type of information can be obtained from molecular simulation using classical force fields.For some classes of MOFs these predictions still pose significant difficulties, namely for MOFs with unsaturated-referred to as 'open'-metal sites [8][9][10][11][12][13][14][15] . These materials crystallize in such a way that both linkers and solvent molecules coordinate to the metal centres.…”
mentioning
confidence: 99%
“…The reason is that an open metal site imposes a chemical environment very different from those considered in the development of these force fields. 12 Ideally, we would use state-of-the-art quantum chemical calculations to evaluate the energy for each state point of a grand canonical Monte Carlo (GCMC) simulation to compute the adsorption isotherm. However, such calculations would require millions of years of central processing unit time.…”
mentioning
confidence: 99%